Enhanced Photoresponse in MoTe2 Photodetectors with Asymmetric Graphene Contacts. Issue 12 (16th April 2019) - Wei, Xia; Yan, Faguang; Lv, Quanshan; Zhu, Wenkai; Hu, Ce; Patanè, Amalia; Wang, Kaiyou
Abstract: Atomically thin 2D materials are promising candidates for miniaturized high‐performance optoelectronic devices. This study reports on multilayer MoTe2 photodetectors contacted with asymmetric electrodes based on n‐ and p‐type graphene layers. The asymmetry in the graphene contacts creates a large ( E bi ∼ 100 kV cm −1 ) built‐in electric field across the short ( l = 15 nm) MoTe2 channel, causing a high and broad (λ = 400–1400 nm) photoresponse even without any externally applied voltage. Spatially resolved photovoltage maps reveal an enhanced photoresponse and larger built‐in electric field in regions of the MoTe2 layer between the two graphene contacts. Furthermore, a fast (∼10 µs) photoresponse is achieved in both the photovoltaic and photoconductive operation modes of the junction. The findings can be extended to other 2D materials and offer prospects for the implementation of asymmetric graphene contacts in future low‐power optoelectronic applications. Abstract : Asymmetric graphene contacts are used to enhance the photoresponse of MoTe2 . The built‐in electric field in the overlapping region of the graphene/MoTe2 /graphene heterostructure enables a high and broad (from 400 to 1400 nm) photoresponse without any externally applied voltage. Also, the short (∼10 nm) MoTe2 channel makes possible a fast (∼10 µs) photoresponse.